1994
DOI: 10.1104/pp.105.1.119
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Activity in the Endosperm of Maize vivipary Mutants

Abstract: During seed maturation the levels of the rate-limiting enzyme of isoprenoid biosynthesis, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMCR) decrease while the levels of the isoprenoid compound abscisic acid (ABA) increase. In the present study, we demonstrate that HMCR specific activity i s inversely correlated with endogenous ABA levels in Zea mays endosperm during seed development. HMCR specific activity and ABA levels were measured in the endosperm of the maize vivipary mutants vp2, vp5, and vp7, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The results of this study showed that exogenous ABA decreases HMGR activity. Consistent with our results, it has reported that HMGR specific activity is inversely correlated with endogenous ABA level in maize endosperm during seed development and in avocado fruit growth (Moore and Oishi 1994;Cowan et al 1997). Also Moore and Oishi (1993) have shown that exogenous ABA inhibits cytosolic HMGR activity in maize roots.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that exogenous ABA decreases HMGR activity. Consistent with our results, it has reported that HMGR specific activity is inversely correlated with endogenous ABA level in maize endosperm during seed development and in avocado fruit growth (Moore and Oishi 1994;Cowan et al 1997). Also Moore and Oishi (1993) have shown that exogenous ABA inhibits cytosolic HMGR activity in maize roots.…”
Section: Discussionsupporting
confidence: 93%
“…In short, we propose that a decline in the CK:ABA ratio lessens sink strength of developing organs by influencing .HMGR and cell division cycle activity to reduce final fruit size. This hypothesis is supported by evidence that shows that ABA retards cell division cycle activity (Müller et al, 1994) and inhibits HMGR activity (Russell and Davidson, 1982;Moore and Oishi, 1994) in severa1 higher plant tissue systems.…”
supporting
confidence: 70%
“…It is well established that ABA increases permeability of lipid membranes (Stillwell and Hester, 1984;Bach, 1986;Stillwell et al, 1989;Purohit et al, 1992;Bürner et al, 1993) and that phytosterols inhibit these ABA-induced perturbations (Stillwell et al, 1990). ABA also appears to inhibit HMGR activity (Russell and Davidson, 1982;Moore and Oishi, 1994). In light of these observations it is tempting to suggest that stress-induced initiation of the ABA signal transduction pathway depresses HMGR activity, limiting synthesis of both CKs and phytosterols to reduce cell-division cycle activity in affected cv Hass fruits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations